Involving young people in decision making about sequential cochlear implantation. (November 2013) - Ion, Rebecca; Cropper, Jenny; Walters, Hazel
Abstract : Background: The National Institute for Health and Clinical Excellence guidelines recommended young people who currently have one cochlear implant be offered assessment for a second, sequential implant, due to the reported improvements in sound localization and speech perception in noise. The possibility and benefits of group information and counselling assessments were considered. Previous research has shown advantages of group sessions involving young people and their families and such groups which also allow young people opportunity to discuss their concerns separately to their parents/guardians are found to be 'hugely important'. Such research highlights the importance of involving children in decision-making processes. Methods: Families considering a sequential cochlear implant were invited to a group information/counselling session, which included time for parents and children to meet separately. Fourteen groups were held with approximately four to five families in each session, totalling 62 patients. The sessions were facilitated by the multi-disciplinary team, with a particular psychological focus in the young people's session. Results: Feedback from families has demonstrated positive support for this format. Questionnaire feedback, to which nine families responded, indicated that seven preferred the group session to an individual session and all approved of separate groups for the child and parents/guardians. Conclusion/discussion: Overall the group format and psychological focus were well received in this typically surgical setting and emphasized the importance of involving the young person in the decision-making process. This positive feedback also opens up the opportunity to use a group format in other assessment processes.